Welfare Problems in Captive Animal Care and their Mitigation (Indian Journal of Animal Production and Management, 2024)
Captive animal welfare can be described as  a state where animals do not exhibit prolonged  negative emotional states and is allowed to express  its natural behaviour while maintaining  homeostasis. Animals that have good mental health  will engage with their environment more, be less  aggressive, less fearful and are more peaceful,  exploratory and active. Such animals will be always  be at ease and adapt well with their surroundings.  Environmental enrichment provides species appropriate challenges, opportunities and  stimulation that promote a range of normal  behaviour pattern in animals. Achieving this quality  of welfare among captive wildlife has numerous  limitations and obstacles that must be addressed by  zoos and other captive facilities. This article  explores the various welfare problems in the care  and management of captive animals as well as their  mitigation techniques and assessment of their  efficiency.
Keywords: welfare; captive wildlife; environmental enrichment; mitigation